1985
DOI: 10.1021/ic00213a025
|View full text |Cite
|
Sign up to set email alerts
|

Bimetallic halides. Crystal structure of and ethylene polymerization by vanadium(II) chloride-zinc chloride-tetrahydrofuran (VCl2.ZnCl2.4THF)

Abstract: h e use of t h e diffractometer. The experimental assistance of J. M. Ball, C. L. Merritt, a n d Dr. S. N a n d a n a a n d Dr. R. Yamdagni's advice a n d help in obtaining spectroscopic data are gratefully acknowledged. We also t h a n k Dr. Scott Collins for helpful discussions.Registry No. meso-1, 97371-16-9; dl-1 (isomer I), 97371-17-0; 2, 81609-97-4; 3, 97295-68-6; [WC13(SMe)], 97295-72-2; [WCI,(SEt)], 97295-74-4; [ WCI,(SPh)], 97295-76-6; Me3Si(SMe), 3908-55-2; Me,Si(SEt), 5573-62-6; Me3Si(SPh), 4551-1 5… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
11
0

Year Published

1988
1988
2010
2010

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(13 citation statements)
references
References 12 publications
2
11
0
Order By: Relevance
“…Thus, a nucleophilic attack of an alkylvanadium species to carbonyl compounds does not readily occur unless stabilizing additive such as HMPA is present . In our alkylation of carbonyl compounds mediated by a dialkylzinc−vanadium system, the reaction of vanadium(III) or -(IV) with R 2 Zn should afford an alkylated Zn−V hetero polymetallic complex similar to those reported by Thiele,3a which may contain both alkylzinc species and vanadium species. The real alkylating reagent may be the alkylzinc part, and the higher-valent vanadium part may function as an activator of the carbonyl compounds by coordination as a Lewis acid.…”
supporting
confidence: 59%
See 1 more Smart Citation
“…Thus, a nucleophilic attack of an alkylvanadium species to carbonyl compounds does not readily occur unless stabilizing additive such as HMPA is present . In our alkylation of carbonyl compounds mediated by a dialkylzinc−vanadium system, the reaction of vanadium(III) or -(IV) with R 2 Zn should afford an alkylated Zn−V hetero polymetallic complex similar to those reported by Thiele,3a which may contain both alkylzinc species and vanadium species. The real alkylating reagent may be the alkylzinc part, and the higher-valent vanadium part may function as an activator of the carbonyl compounds by coordination as a Lewis acid.…”
supporting
confidence: 59%
“…Although it is known that dialkylzinc reagents, R 2 Zn, are generally inert to carbonyl compounds, addition of a catalytic amount of an amino alcohol or certain transition metal complexes can enhance their nucleophilicity and make them reactive toward carbonyl compounds. It is reported that R 2 Zn can reduce vanadium(IV) complexes and produce low-valent vanadium(II) species, but application of the latter to organic synthesis has not appeared so far. During the course of our study to examine the reactivity of the combination of R 2 Zn and several vanadium complexes, we have found that reagents derived from R 2 Zn and VCl 4 or VCl 3 (thf) 3 showed different reactivity toward carbonyl compounds depending on the reaction conditions for preparation of the reagents.…”
mentioning
confidence: 99%
“…Studies of the oxidation state of vanadium catalysts for ethylene polymerization have generally revealed that V(III) and V(IV) precursors are often reduced to inactive V(II) species [9][10][11][12]. Alkyl vanadium(III) complexes bearing amidinate [13,14] and amide [15,16] ligands produce shortlived ethylene polymerization catalysts and are inactive in propene polymerization.…”
Section: Introductionmentioning
confidence: 99%
“…Studies of the oxidation state of active vanadium catalysts for ethylene polymerization by different investigators has led to the proposal that V iii and V ii represent the important oxidation states in the ethylene polymerization process. 8,9 Herein we report the synthesis, structural characterization and catalytic activity of the vanadium(iii) heterodinuclear complexes [V(m-DIPP) 2 {O(CH 2 CH 2 S) 2 }Li(L) 2 ] 1, 2 and the mononuclear complex 4) Å, within the range expected for V-S single bonds and comparable to other vanadium(iii) thiolato complexes. [12][13][14][15] The X-ray analysis of 3 reveals a mononuclear complex [V(DIPP){O(CH 2 CH 2 S) 2 }(py)] with slightly distorted trigonalbipyramidal coordination around the vanadium centre (Fig.…”
mentioning
confidence: 73%